Natura tax di Indonesia ditinjau dari aspek sosiologi hukum dan dampaknya terhadap pengelolaan perpajakan - Mahpudin, Endang; Hidayat, Udin; Nurdiana, Mardi; Hasyim, Abdul; Purwaji, Ade; Hidayat, Anwar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2024)
This article analyzes the application of tax on the provision of natura from the employer to employee in the aspect of legal sociology, so that it can be seen how the application of tax regulations for taxpayers. Through normative juridical analysis, the legal framework and tax provisions are analyzed based on references to the enactment of the in-kind tax. The author comes to the conclusion that tax provisions can change how the society would behave, especially taxpayers in carrying out their taxation, because taxpayers will try to carry out their obligations efficiently and avoid larger payments, thus it can also have an impact on how taxpayers carry out tax management in accordance with applicable regulations.